GAMBARAN PERILAKU ORANG TUA DALAM MEMBAWA ANAK IMUNISASI SELAMA MASA PANDEMI COVID-19 - Jayanti, Ni Wayan Radha Rani; Devi, Ni Luh Putu Shinta; Puspita, Luh Mira (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p15, 2023)
During the Covid-19 pandemic, the coverage of basic and advanced immunizations decreased. The purpose of this study was to describe the behaviour of parents in bringing their children immunized during the Covid-19 pandemic in the work area of Puskesmas III Denpasar Selatan. This study was a descriptive quantitative study with a cross sectional approach. The sampling technique was used non-probability sampling with purposive sampling technique. The sample used 71 parents which have babies and toddlers with the age of 0-24 months. The data were collected in the work area of Puskesmas III Denpasar Selatan for one month from March to April 2022. The research instruments used were Immunization Behavior Questionnaire during the Covid-19 pandemic. The result showed that most parents who have babies and toddlers aged of 0-24 months in the work area of Puskesmas III Denpasar Selatan have good immunization during the Covid-19 pandemic. Health service facilities are expected to be able to provide immunization services according to the technical instruction for immunization services during the Covid-19 pandemic so that parents feel safe when bringing their children for immunization.